Letter from Nanette Bolton to James Curtis Booth, January 28, 1882 - Bolton, Nanette (1882)
Nanette Bolton, a relative of James Curtis Booth (1810-1888) asks Booth to help find employment for her son, Robert Bolton.
Keywords: Booth, James Curtis, 1810-1888; Bolton, Nanette